Unlocking the Secrets of Earth and the Universe: Recent Advances in Earth and Space Physics - Kastwar, Parul (Journal of Advanced Research in Geo Sciences & Remote Sensing, 2024)
Earth and space physics encompasses a broad range of phenomena that involve the interacti ons between Earth’s environment and the broader space weather system. This fi eld is vital for understanding how solar acti vity, cosmic rays, and the Earth’s magneticfield infl uence both terrestrial and space-based technologies, as well as broader climate processes. Recent advancements in observati onal techniques, such as satellite missions, ground-based instruments, and computati onal modeling, have significantly enhanced our understanding of the magnetosphere, ionosphere, solar wind, and cosmic radiation. These developments have not only provided insights into space weather events like geomagneticstorms and solarflares but have also paved the way for better predicti ons and miti gati on strategies for their potential impacts on communication, navigation, and power systems. Additionally, the study of cosmic rays and the interplanetary mediumis critical for safeguarding human space exploration missions beyond low Earthorbit. This review highlights the current state of knowledge in Earth and space physics, summarizing key discoveries, ongoing challenges, and future research directions, with a focus on the Sun-Earth connection, space weather forecasting, and the protection of space infrastructure and human health in space.